1965
DOI: 10.1039/tf9656102223
|View full text |Cite
|
Sign up to set email alerts
|

Entropies of aqueous ions

Abstract: From a study of entropy changes for complex ions support has been found for Gurney's result that the standard partial molar entropy of the hydrogen ion (Sit) has an absolute value of --5 5 cal/g ion deg. On this basis, other absolute ionic values can be deduced for standard partial molar entropies So, entropies of transport S*',-and transported entropies 3". A plot of 5' against S" for a variety of ions indicates that S*" and increase stepwise with numerical charge and that, on the basis of the above datum for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

1971
1971
1984
1984

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…7a (18). This is due to the well-known autocomplexation that o'ccurs in zinc halide solutions as indicated by EMF, thermal and Raman spectroscopic experiments (18,23,28). Thus, Shchukarev et al (29) reported widely different TAS values for the formation of ZnBr § ZnBr2, ZnBr3-, and ZnBr42-complex ions.…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…7a (18). This is due to the well-known autocomplexation that o'ccurs in zinc halide solutions as indicated by EMF, thermal and Raman spectroscopic experiments (18,23,28). Thus, Shchukarev et al (29) reported widely different TAS values for the formation of ZnBr § ZnBr2, ZnBr3-, and ZnBr42-complex ions.…”
Section: Discussionmentioning
confidence: 94%
“…The latter are quite reliably known for most simple ions from extra-thermodynamic procedures (1,22,23) but the S~ E values, which are not negligible at appreciable concentrations, are not so easily evaluated in a reliable way. Recourse may be had to data calculated from the Debye-H~ickel theory, based on Kielland's work (26), for dilute solutions, but for elevated concentrations where ion size and hydration effects become important (27) in determining T~, the required derivative d In T~/dT is difficult to evaluate.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations